Esthetic and Functional Outcomes of Superficial Parotidectomy Comparing Three Reconstruction Techniques: An Interventional Clinical Study - Sherif Mohammad Askar; Abd ElRaof Said Mohamed; Tamer Oraby; Ibrahim Khaled; Mahmoud Megahed; Ali Awad (International Archives of Otorhinolaryngology)
Introduction Preauricular defect is one of the main concerns after superficial parotidectomy. Plastic surgeons have described many filling techniques to overcome the problem.